Формування вмінь продукування вторинних текстових повідомлень у молодших школярів з недорозвиненням мови - Святенко, Сергій Віталійович (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Мета дослідження: теоретично обґрунтувати, розробити й експериментально перевірити методика формування вмінь продукування вторинних текстових повідомлень у молодших школярів з недорозвиненням мови.

Research aim: to theoretically substantiate, design, and experimentally test a methodology for developing the skills of producing secondary textual messages in primary school children with speech underdevelopment.
Developing the Skills of Producing Secondary Textual Messages in Primary School Children with Speech Underdevelopment
Keywords: SOCIAL SCIENCES::Social sciences::Pedgogical work; молодші школярі; загальне недорозвинення мови; вторинні тестові повідомлення; методика формування вмінь продукування вторинних текстових повідомлень; primary school children; general speech underdevelopment; secondary textual messages; methodology for developing skills of producing secondary textual messages